ON THE ANALYSIS OF ETHNONAMES - Maftuna , Safarova Zoir qizi (Educational Research in Universal Sciences, 2023)
This article discusses the motivations, reasons and etymology of the names of clans and tribes. The spiritual classification in the formation of ethnonyms is shown.